2020
DOI: 10.1289/ehp5445
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use Change and Cardiometabolic Risk Factors in an Urbanizing Area of South India: A Population-Based Cohort Study

Abstract: BACKGROUND: Land-use changes in city fringes due to urbanization can lead to a reduction of greenspace that may reduce its associated health benefits. OBJECTIVES: We evaluated the association between changes in residential surrounding built-up land use and cardiometabolic risk factors in an urbanizing peri-urban area of south India and explored the mediating roles of air pollution, physical activity, and stress in these associations. METHODS: We analyzed data on 6,039 adults from the third follow-up of the And… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Alternatively, a true effect of the intervention in adolescence may been attenuated over the long-term follow-up due to nutrition or economic transition [6,7], which would support the view that the risk of cardiovascular disease accumulates across the life course [17]. Between 1991 and 2011, the population of study villages increased by 31% (census data), and NTLI and built-up land use (both from remote sensing data) increased by 156% and 196%, respectively, confirming urbanisation of the study villages, which was also found to be associated strongly with cardiovascular risk factors in APCAPs participants [24]. There was some support for this hypothesis from models stratified by urbanisation, which showed weak evidence of the effect of intervention in the least urbanised villages (S3 Table).…”
Section: Comparison With Previous Researchmentioning
confidence: 52%
“…Alternatively, a true effect of the intervention in adolescence may been attenuated over the long-term follow-up due to nutrition or economic transition [6,7], which would support the view that the risk of cardiovascular disease accumulates across the life course [17]. Between 1991 and 2011, the population of study villages increased by 31% (census data), and NTLI and built-up land use (both from remote sensing data) increased by 156% and 196%, respectively, confirming urbanisation of the study villages, which was also found to be associated strongly with cardiovascular risk factors in APCAPs participants [24]. There was some support for this hypothesis from models stratified by urbanisation, which showed weak evidence of the effect of intervention in the least urbanised villages (S3 Table).…”
Section: Comparison With Previous Researchmentioning
confidence: 52%
“…Both variables are crucial in understanding urban green space usage in the context of Dhaka. With increasing noncommunicable disease burdens in Dhaka and the overall Global South [96,97,117,118], more people are being diagnosed with NCDs, such as diabetes and cardiovascular disease. Healthcare professionals often recommend outdoor physical exercise for such patients in addition to regular medications, resulting in more patients engaging in health promotion in green spaces through active (moderate to vigorous physical activity) and passive activities (social gatherings, nature viewing).…”
Section: General Findingsmentioning
confidence: 99%
“…Nevertheless, these findings are intriguing in the context of globalisation and changing social conditions in both urban and rural areas and warrant further research. Policy interventions in India have so far focussed on limited aspects of dietary intake (e.g., advertising and labelling of junk food); we suggest that these should be extended and expanded to include interventions aimed at increasing physical activity in urban areas, such as improving walkability of streets and green spaces, although there could be challenges to such approaches because of increasing pollution levels or rapid urbanisation of areas causing a decrease in green spaces [36]. Migrants, particularly in the workplace, are a readily identifiable group, who might be more motivated to take part in on-site health promotion activities, including healthy canteen lunches and exercise classes [7,37].…”
Section: Implications and Further Researchmentioning
confidence: 99%